Microbial activity in soil enriched with preparations of AS-lignin and lignofulvonic acid - Kunc, F; Rybárová, J (Folia microbiologica, 1977)
In chernozem soil, enriched with preparations of AS-lignin or lignofulvonic acid, an increased production of carbon dioxide was observed during a 4-week incubation, and, as compared with the non-amended control, an increased number of bacteria but not of actinomycetes was detected. Increased numbers of fungi were detected only in the variant with AS-lignin at the end of the incubation. The relative incidence of bacteria utilizing vanillin, syringic acid or protocatechuic acid as the only carbon sources increased in the enriched medium. Oxidation of vanillic acid, syringic acid and to a lesser extent of coumarin increased in suspensions of soils incubated with AS-lignin or fulvic acid. The results obtained indicate that bacteria are involved in the mineralization of the added substrates and confirm the relationship between metabolism of these compounds and simple aromatic derivatives.
Keywords: Actinomycetaceae; Fungi; oxid uhličitý; benzopyrany; půdní mikrobiologie; Bacteria; houby; Carbon Dioxide; půda; lignin; Benzopyrans; Lignin; Soil Microbiology; Soil